Statistics Reform in Africa : Aligning Incentives with Results - Hoogeveen, Johannes; Nguyen, Nga Thi Viet (Taylor and Francis, 2019)
While there is a strong association between limited capacity and unavailability or production of low quality statistics in Africa, poor incentives are argued to be behind Africa’s statistical tragedy. The paper explores whether incentives of leaders and donors are aligned with the production of quality statistics and proposes six concrete ways to improve the current situation.